Autonomic and Cognitive Function Response to Normobaric Hyperoxia Exposure in Healthy Subjects. Preliminary Study - Kujawski, Sławomir (Medicina (Kaunas), 2020)
Background and objective: This is the first study to investigate the effect of high-flow oxygen therapy, using a normobaric chamber on cognitive, biochemical (oxidative stress parameters and the level of neurotrophins), cardiovascular and autonomic functioning. Materials and methods: 17 healthy volunteers, eight males and nine females, with a mean age of 37.5 years, were examined. The experimental study involved ten two-hour exposures in a normobaric chamber with a total pressure of 1500 hPa (32–40 kPa partial pressure of oxygen, 0.7–2 kPa of carbon dioxide and 0.4–0.5 kPa of hydrogen). Cognitive function was assessed by using Trail Making Test parts A, B and difference in results of these tests (TMT A, TMT B and TMT B-A); California Verbal Learning Test (CVLT); Digit symbol substitution test (DSST); and Digit Span (DS). Fatigue (Fatigue Severity Scale (FSS)), cardiovascular, autonomic and baroreceptor functioning (Task Force Monitor) and biochemical parameters were measured before and after intervention. Results: After 10 sessions in the normobaric chamber, significant decreases in weight, caused mainly by body fat % decrease (24.86 vs. 23.93%, p = 0.04 were observed. TMT part A and B results improved (p = 0.0007 and p = 0.001, respectively). In contrast, there was no statistically significant influence on TMT B-A. Moreover, decrease in the number of symbols left after a one-minute test in DSST was noted (p = 0.0001). The mean number of words correctly recalled in the CVLT Long Delay Free Recall test improved (p = 0.002), and a reduction in fatigue was observed (p = 0.001). Biochemical tests showed a reduction in levels of malondialdehyde (p < 0.001), with increased levels of Cu Zn superoxide dismutase (p < 0.001), Neurotrophin 4 (p = 0.0001) and brain-derived neurotrophic factor (p = 0.001). A significant increase in nitric oxide synthase 2 (p = 0.02) and Club cell secretory protein (p = 0.015) was also noted. Baroreceptor function was significantly improved after normobaric exposures (p = 0.003). Significant effect of normobaric exposures and BDNF in CVLT Long Delay Free Recall was noted. Conclusions: This study demonstrates that 10 exposures in a normobaric chamber have a positive impact on visual information and set-shifting processing speed and increase auditory-verbal short-term memory, neurotrophic levels and baroreceptor function. A response of the respiratory tract to oxidative stress was also noted. There is a need to rigorously examine the safety of normobaric therapy. Further studies should be carried out with physician examination, both pre and post treatment.